2021
DOI: 10.1364/ol.425372
|View full text |Cite
|
Sign up to set email alerts
|

Engineering spatial correlations of entangled photon pairs by pump beam shaping

Abstract: The ability to engineer the properties of quantum optical states is essential for quantum information processing applications. Here, we demonstrate tunable control of spatial correlations between photon pairs produced by spontaneous parametric down-conversion, and measure them using an electron multiplying charge coupled device (EMCCD) camera. By shaping the spatial pump beam profile in a type-I collinear configuration, we tailor the spatial structure of coincidences between photon pairs entangled in high dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…As can be seen, there is excellent agreement between our experimental results and the expected spatial cross-correlation patterns obtained from the simulation. These results show that it is possible to achieve arbitrary spatial distributions in the twin beam correlations and, thus, represent a substantial advancement with respect to previous proof-of-principle experiments with PDC (20,22).…”
Section: Control Of Distribution Of Spatial Correlationsmentioning
confidence: 64%
See 1 more Smart Citation
“…As can be seen, there is excellent agreement between our experimental results and the expected spatial cross-correlation patterns obtained from the simulation. These results show that it is possible to achieve arbitrary spatial distributions in the twin beam correlations and, thus, represent a substantial advancement with respect to previous proof-of-principle experiments with PDC (20,22).…”
Section: Control Of Distribution Of Spatial Correlationsmentioning
confidence: 64%
“…This is achieved through a complete control of the spatial correlations in the twin beams generated using FWM with a phase-structured pump beam. The degree of control that we are able to obtain is key to enable information encoding in the form of a target spatial distribution and is a substantial advancement over previous experiments with PDC (20,22). Furthermore, the information cannot be read out from either of the individual beams, and the additional use of a constant-phase region at the center of the CGH prevents the information from being present in the bright spatial profiles of the generated twin beams.…”
Section: Discussionmentioning
confidence: 99%
“…The wave function is controllable by the spectrum of the pump, similar to the case in conventional nonlinear crystals [10] . Note that this control is weighted by the SPDC efficiency function.…”
Section: Spdc From Lithium Niobate Nonlocal Metasurfacementioning
confidence: 97%
“…For nonlinear crystals with a typical thickness on the scale of millimeters to centimeters, the stringent phase-matching condition limits the emission directions of the photon pairs to a certain predefined angle range, making it difficult to flexibly tune the spatial pattern and entanglement of the photon pairs while maintaining generation efficiency. Although control of spatial correlations of the photon pairs was recently reported by engineering the pump beam profile [10] , the specific tuning range of the spatial entanglement was unknown. It was shown that strong multimode entanglement can be achieved in thin nonlinear films [11] ; however, the generation efficiency was much weaker compared to conventional schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Coincidence imaging can be achieved with modern EMCCD cameras [31,32], SPAD arrays [33][34][35] or time stamping cameras [36]. These technologies are commonly exploited in quantum imaging, such as ghost imaging experiments [37][38][39][40] or quantum superresolution [41][42][43], as well as for fundamental applications, such as characterizing two-photon correlations [32,44], imaging of high-dimensional Hong-Ou-Mandel interference [45][46][47][48], and visualization of the violation of Bell inequalities [49]. Holography techniques have been recently proposed in the context of quantum imaging [50,51]; demonstrating the phaseshifting digital holography in a coincidence imaging regime using polarization entanglement [50], and exploiting induced coherence, i.e.…”
Section: Introductionmentioning
confidence: 99%